Eletrical installation calculation : advanced :. Level 3 : for technical certificate and NVQ level 3 / Christopher Kitcher and A.J. Watkins - Kitcher, Christopher
Proved an invaluable reference for over forty years, for both apprentices and professional electrical installation engineers alike. The book provides a step-by-step guide to the successful application of electrical installation calculations required in day-to-day electrical engineering practice